Ocenjevanje zahtevnosti postopkov - Vajde Horvat, Romana (Strojniški vestnik, 2001)
All types of processes can be described as a sequence of activities using a set of reqiured input and output products and resources of different types. Knowing the process in detail ensures that evaluations of the required effort for projects - conducted on the basis of a described process model - are more accurate. The Software Process Complexity Model (SoPCoM) described in this paper provides a mechanism for the description of a process in Petri-nets notation. Attributes defined in the SopCoM enable an evaluation of the complexity of each process element as well as the complexity of the process as a whole. The relative complex process model. The SoPCoM was developed at the University of Maribor.
Keywords: postopki; modeli postopkovni; zahtevnost postopkov; mreže Petri; modeliranje; Petrijeve mreže